Tourism development planning in local level government: A proposal for Devdaha Municipality, Nepal - Tamang, Bal Bahadur (Journey for Sustainable Development and Peace Journal, 2023)
Tourism development has been a prominent issue in Nepal’s development. With the promulgation of a new Constitution in 2015 and federal delineation in the country, the local governments have been further provided with the rights of development planning and implementation. In this context, tourism has been an unavoidable part of development planning at the local levels. This paper is based on the case study of the tourism development plan of Devdaha municipality of Rupandehi, Lumbini province. Following both primary and secondary sources of data, this paper discusses different potentialities, challenges, policies, strategies and action plans for 10 years (2023-2033). The plan prepared for the tourism development gives a guideline for bringing about changes in the tourism sector in this Municipality.